Impact of crystal structure on optical properties and temperature sensing behavior of NaYF4:Yb3+/Er3+ nanoparticles - Dubey, Charu; Yadav, Anjana; Baloni, Diksha; Kachhap, Santosh; Singh, Sunil Kumar; Singh, Akhilesh Kumar (Royal Society of Chemistry, 2023)
We report a comprehensive study of the structural, morphological, and optical properties, and UC-based ratiometric temperature sensing behavior of (α) cubic and (β) hexagonal phases of NaYF4:Yb3+/Er3+ nanoparticles. The α-NaYF4:Yb3+/Er3+ and β-NaYF4:Yb3+/Er3+ nanoparticles were synthesized using co-precipitation and hydrothermal methods, respectively. Powder X-ray diffraction studies confirmed the phase purity of the samples. The morphological studies show uniform particle sizes of both phases; the average particle size of α-NaYF4:Yb3+/Er3+ and β-NaYF4:Yb3+/Er3+ was 9.2 nm and 29 nm, respectively. The Raman spectra reveal five sharp peaks at 253 cm−1, 307 cm−1, 359 cm−1, 485 cm−1, and 628 cm−1 for β-NaYF4:Yb3+/Er3+, whereas α-NaYF4:Yb3+/Er3+ shows two broad peaks centred at 272 cm−1 and 721 cm−1. The optical property measurements show that α- and β-NaYF4:Yb3+/Er3+ phases have distinct upconversion emission and temperature sensing behavior. The upconversion emission measurements show that β-NaYF4:Yb3+/Er3+ has higher overall emission intensities and green/red emission intensity ratio. The temperature-dependent upconversion emission measurements show that α-NaYF4:Yb3+/Er3+ has higher energy separation between 2H11/2 and 4S3/2 energy states. The temperature sensing performed utilizing these thermally coupled energy levels shows a maximum sensitivity of 0.0069 K−1 at 543 K and 0.016 K−1 at 422 K for β-NaYF4:Yb3+/Er3+ and α-NaYF4:Yb3+/Er3+, respectively.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Crystal structure; Nanoparticles; Optical properties; Precipitation (chemical); Synthesis (chemical); Temperature sensors